Work conditions and masked (hidden) hypertension—insights into the global epidemic of hypertension - Landsbergis, Paul A.; Schnall, Peter L.; Belkić, Karen L.; Schwartz, Joseph E.; Baker, Dean; Pickering, Thomas G. (SJWEH Supplements, 2008)
Hypertension is the leading cause of cardiovascular disease. There is considerable evidence that work conditions play an important role in the etiology of essential hypertension. Ambulatory blood pressure during waking hours (work and home) is more strongly associated with subsequent cardiovascular disease than the traditional measurement of casual clinical blood pressure. A person with normal clinical blood pressure but elevated awake ambulatory blood pressure is said to have “masked” (or “occult” or “hidden”) hypertension. Masked hypertension is associated with increased cardiovascular risk, and has been observed in 10–30% of adults with normal clinical blood pressure. It has been hypothesized that exposure to workplace stressors first elevates work, but not clinical, blood pressure; after chronic exposure to stressors, both daytime and clinical pressure become elevated. In this manuscript, an algorithm is provided that targets ambulatory monitoring for high-risk groups and helps detect work-related hypertension. A public health approach incorporating clinical guidelines, workplace surveillance, and improved work conditions is recommended for tackling the epidemic of hypertension.
Keywords: ambulatory blood pressure; epidemic; epidemiology; hidden hypertension; hypertension; job strain; masked hypertension; occult hypertension; review; white-coat hypertension; work conditions; work stress